A formula(ação) de uma política pública para a juventude: propósito, atores e percepções do Programa Estadual Agente Jovem Ambiental (AJA) na zona costeira do Ceará, Brasil - Nascimento, Hermógenes Henrique Oliveira (2025)
The Young Environmental Agent Program (AJA, in the acronym in Portuguese) is a public policy in the state of Ceará created by State Law No. 17,383/2021 with the mission of inserting young people in vulnerable situations into society to work on socio-environmental projects in their communities. The present work has the purpose of analyzing the formulation, application, and effectiveness of the AJA Program based on the parameters of sustainable development based on the environmental, social, economic, and institutional dimensions, as well as the effectiveness of such parameters, especially for the spatial outline of the coastal zone of Ceará. The scope and structure of the thesis were divided into 3 sections. The research began with the presentation of the methodological and theoretical framework necessary to support the line of defense of the thesis. The procedures adopted had a qualitative-quantitative approach with an exploratory bias. The general argumentative conception was supported by content and critical discursive analysis. The statistical dimension was given through the collection of primary and secondary data, in addition to having an estimated sample population of 1217 young environmental agents residing in these coastal municipalities. To this end, the first article included the analysis of community action plans based on global sustainability indicators, highlighting adherence to Sustainable Development Goals (SDGs) 3 and 11, originating from the 2030 Agenda. Then, anchored in the concepts of public management and its applications, the study initially showed the moderate adherence of such indicators for the protection of coastal territories in Ceará. In this step, the article concluded by detecting that the program still faces logistical and financial resource problems that make it difficult for young people to work. As a suggestion to resolve these impasses, partnerships with municipal public management should be strengthened. In relation to the second article, we sought to rethink a new structural arrangement of the program based on the perceptions and experiences of the young participants. Based on the state legislation creating the AJA Program and based on other experiences, it was possible to understand whether this public policy has achieved its creation objectives contained in the law. Likewise, it analyzed which sustainability indicators arising from the SDGs of the 2030 Agenda were linked to the reality of the AJA to then understand how environmental governance criteria impacted the delimitation of such policies, incorporated into the agendas of young environmental agents and government agendas. As a conclusion of the second article, it was extracted from the questionnaire responses that young people are more focused on the theme of environmental education through the actions proposed in their projects. This article also highlighted the need for the AJA Program to be attentive to new socio-environmental demands. Finally, a series of adjustments and measures were recommended to increase the effectiveness of this public policy. With the aim of bringing the state and society closer together in favor of strengthening the participatory management of the program and improving the quality of life of communities. It is also expected that more and more young people will be involved in state public policies and will be protagonists of their own history in the environmental scenario of Ceará.